Citizenship-Oriented Care: Increasing Voting Participation in a Mental Health Trust - Cissy Atwine; Emily Cobb; Oliver Dale (BJPsych Open, 2025)
Aims: The overall aim of this project was to encourage mental health patients to participate in the general election. To raise awareness among staff about patient voting rights so they are better equipped to encourage patients to participate.